PERBEDAAN MODEL PEMBELAJARAN GEOGRAFI: PROJECT BASED LEARNING DENGAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA DALAM KURIKULUM 2013 DI SMAN 112 JAKARTA BARAT - Annisa Salsabilla; Eko Tri Rahardjo; Ode Sofyan Hardi (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2014)
ABSTRACT This study aims to obtain empirical data whether there is any difference in student result between students who use a geographic model of project-based learning with students who use a model of problem-based learning in the curriculum in 2013. Research using experimental methods. The population of this study are all tenth grade social studies in SMA 112 West Jakarta. While the sample in this study are two classes of tenth grade social studies in SMA 112 West Jakarta which has not much different of student result in geography, obtained by X IPS 2 as an experimental class using a model of problem-based learning and X IPS 3 as an experimental class using a model of project-based learning. This research instrument are 24 questions of pre-test and post-test with 5 multiple choices. Before the instrumen is used, there is validity testing using Pearson with SPSS 19.0. From these calculation obtained 24 valid instruments and 6 invalid instruments. Testing requirements analysis conducted prior to hypothesis testing, are test for normality and homogeneity tests. Normality test using the Liliefors test, from the calculation obtained significance value of class using the model of projectbased learning = 0,94, and a significance value of class using the model of problem-based learning = 0,11, each of the significance value > 0,05. Homogeneity test using One-Way Annova test, values that obtained from the calculation of the probability = 0.264 is greater than the significance level = 0.05. Based on tests of normality and homogeneity test can be concluded that the data derived from a homogeneous population and a normal distribution. Hypothesis testing using t-test formula two parties, of the calculation obtained t-count = 2.200 is greater than the t-table = 2.020. This proves that hypothesis Ha is accepted. Therefore, the results of this study concluded that there is a difference between model of project-based learning with problem-based learning model of the student results of geography in the curriculum in 2013, where the model of project-based learning is more suitable when used in disaster mitigation material because this model has the advantage in the dimensions of the conceptual knowledge not owned by a model of problem based learning Keywords: Models of Learning, Project Based Learning, Problem Based Learning.